2012
DOI: 10.1590/s0073-47212012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, breeding and food of the Little Blue Heron Egretta caerulea (Aves, Ardeidae) in the Patos Lagoon estuary, a recently colonized area in southern Brazil

Abstract: ABSTRACT. We document the expansion of the breeding distribution of the Little Blue Heron Egretta caerulea (Linnaeus, 1758) to 850 km beyond its previous southern limit in South America. In addition we present data on abundance, breeding biology and food of the species in the Patos Lagoon estuary, the area which the species recently colonized. The maximum abundance recorded in the breeding colony and in a nocturnal roosting site was 53 and 49 individuals respectively. Nesting occurred from September to March.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
10
0
9
Order By: Relevance
“…Porém, novos registros têm sido feitos ampliando sua área de ocorrência em Santa Catarina (CREMER; GROSE, 2010;GIANUCA, et al, 2011). Recentemente, Gianuca et al (2011) relataram a presença de colônias de N. violacea em Itajaí, assim como em Florianópolis.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Porém, novos registros têm sido feitos ampliando sua área de ocorrência em Santa Catarina (CREMER; GROSE, 2010;GIANUCA, et al, 2011). Recentemente, Gianuca et al (2011) relataram a presença de colônias de N. violacea em Itajaí, assim como em Florianópolis.…”
Section: Discussionunclassified
“…Estudos no Brasil mostram que esta agregação pode concentrar de poucos pares (MATOS, 1996;RECHETELO, 2009;GIANUCA, et al, 2011) (GIANUCA, 2010). Segundo Kushlan (1977), o tamanho da população reprodutiva é resultado da relação entre o local escolhido, a disponibilidade de alimento, a distância do local para a área de forrageio a abundância disponível de presas (ERWIN et al, 1996).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Sampling efforts on anuran (Quintela et al 2007, Bernardo-Silva et al 2012, Dalmolin et al 2017, reptilian (Quintela et al 2011) and avian fauna (Gianuca et al 2007(Gianuca et al , 2008(Gianuca et al , 2012 in the insular environments have identified the occurrence of some unexpected taxa for the region, including the southernmost and isolated population of the threatened red-bellied toad Melanophryniscus dorsalis (Mertens, 1933) (Quintela et al 2006, Bernardo-Silva et al 2012. While some groups such as herpetofauna and avifauna are relatively well-known in the island, the ichthyofauna remained practically unexplored.…”
Section: Introductionmentioning
confidence: 99%